Estrategias lúdicas para el desarrollo de la atención en niños de 3 a 4 años en la Escuela de Educación Básica San Mateo de la ciudad de Riobamba - Jácome Rivera, Adriana Elizabeth (2024)
The general objective of this research work entitled Playful Strategies for the development of attention in children from 3 to 4 years old in the San Mateo Basic Education School in the city of Riobamba, has the general objective of analyzing playful strategies as effective tools for the development of attention in children from 3 to 4 years old in the aforementioned educational institution. To achieve this objective, a quantitatively oriented methodology was applied, using a non-experimental design and a bibliographic approach. In this way, it was configured as a field study, allowing reliable data to be obtained from the real environment of the institution through the observation technique. This technique focused on how play can make it easier for students to develop attentional skills. An observation sheet was developed with specific indicators to evaluate the behavior and development of the students concerning the topic of study. The sample of this study was composed of a total of 9 children, 5 girls, and 4 boys, belonging to Initial Level 1 and aged between 3 and 4 years. After making the corresponding observation, it could be seen that most of the children do not have an adequate development of their attention. In addition, when analyzing the teacher’s behavior and actions in specific situations within the classroom, it was observed that the teacher failed to include activities focused on the development of attention. Finally, after analyzing the results of the observation, a set of playful strategies has been incorporated for the development of children’s attention. This proposal not only promotes significant improvements in their psychomotor skills but also contributes to improving their ability to focus on specific tasks and filter out distractions.